Variabilita TLR2 receptoru u hrabošovitých hlodavců (Arvicolidae) napříč Evropou, v závislosti na parazitovanosti hostitele. - Charvátová, Klára (Jihočeská univerzita, 2018)
This study investigates phylogenetic variability of the immune receptor TLR2 in arvicolid rodents from seven European countries. The variability was tested based on the presence or absence of ectoparasitic lice of the genus Hoplopleura and endoparasitic coccidia of the genus Eimeria.
Variability of the TLR2 receptor in arvicoline rodents (Arvicolidae) across Europe depending on parasitation of the host.